Treatment Related Hematologic Changes in a Population of Iranian Patients with Chronic Hepatitis C Infection from 2009 to 2014 - Zahra AHMADINEJAD; Zahra ABDILIAEI; Rizan MOHAMADI; Omid REZAHOSSEINI (Tehran University of Medical Sciences, 2017)
Background: We aimed to assess the frequency of hematologic changes, response to treatment, rate of discontinuation and dose reduction in Hepatitis C positive patients, treated with Interferon and ribavirin from Apr 2009 to Mar 2014. Methods: In this cross-sectional study, out of registered patients, 554 were assessed and 150 patients with positive HCV PCR, regular patient visits to clinic and complete records were included. HCV viral load, complete blood count and liver enzyme levels were measured before initiation of treatment and monthly.. Exclusion criteria's were other types of hepatitis and HIV infection, autoimmune or blood diseases, illegal drug use and treatment with bone marrow suppressors. The data was analyzed using SPSS. Results: Out of 150 patients, 135 (90%) were male. Mean age was 39.7± 10.7 (range 23-74) yr old. Forty-six patients (30.7%) had genotype 1 and 99 (66%) genotypes 2 and 3. Treatment regimens were prescribed as Pegafron+Ribavirin in 125 (83.3%), Interfron+Ribavirin 9 (6%) and Pegintron+Ribavirin in 16 (10.7%) of patients... The prevalence of anemia in genotype 1 patients was higher (P=0.044). There was no association between sex and leukocyte changes.  Thirty-four (22.7%) patients had moderate and severe thrombocytopenia. Six patients had severe anemia and Ribavirin dose was adjusted. Conclusion: The hematological changes are common side effects of conventional hepatitis C treatment regiments. Although drug dose adjustment is not usually necessary, due to severe anemia in genotype 1 patients, we should treat high-risk patients cautiously and made the appropriate changes in drug dosage at the right time.